2010
DOI: 10.1002/ps.2030
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of Chrysoperla carnea complex and Chrysopa spp. lacewings (Neuroptera: Chrysopidae) to aphid sex pheromone components and a synthetic blend of floral compounds in Hungary

Abstract: As the floral bait alone attracted both sexes of the carnea complex, it showed potential to manipulate the location of larval density via altering the site of oviposition. Aphid sex pheromone compounds alone attracted predatory males of Chrysopa spp. and can potentially be used to enhance biological control of aphids. For the carnea complex, however, a combination of both baits is not advantageous because of the decrease in adults attracted. Assumptions of intraguild avoidance underlying this phenomenon are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…La localización de sus presas a través de sus secreciones, kairomonas, alomonas y/o feromonas ha sido frecuentemente registrada, y sobre ellas pueden llegar a ser extremadamente voraces (Withycombe, 1925;Principi, 1954bPrincipi, , 1984Tjeder, 1966;Canard, 1973aCanard, , 1973bWattebled et al, 1978;Samson & Blood, 1979Canard & Duelli, 1984;New, 1986aNew, , 1988aNew, , 1989New, , 2001Duelli, 1987b;Frazer, 1988;Szentkirályi, 1989Szentkirályi, , 2001aMcEwen et al, 1993aMcEwen et al, , 2001Růžička, 1994Růžička, , 1997aRůžička, , 1997bRůžička, , 1998Růžička, , 2010Mendel et al, 1997Mendel et al, , 2004Boo et al, 1998Boo et al, , 1999Boo et al, , 2003Bakthavatsalam & Singh, 1999;Nelson et al, 2001;Canard & Volkovich, 2001;Penny, 2002;Branco et al, 2006aBranco et al, , 2006bSchwartzberg et al, 2008;Koczor et al, 2010Koczor et al, , 2015.…”
Section: Datos Generales Sobre Su Biología Comportamiento Estadios unclassified
“…La localización de sus presas a través de sus secreciones, kairomonas, alomonas y/o feromonas ha sido frecuentemente registrada, y sobre ellas pueden llegar a ser extremadamente voraces (Withycombe, 1925;Principi, 1954bPrincipi, , 1984Tjeder, 1966;Canard, 1973aCanard, , 1973bWattebled et al, 1978;Samson & Blood, 1979Canard & Duelli, 1984;New, 1986aNew, , 1988aNew, , 1989New, , 2001Duelli, 1987b;Frazer, 1988;Szentkirályi, 1989Szentkirályi, , 2001aMcEwen et al, 1993aMcEwen et al, , 2001Růžička, 1994Růžička, , 1997aRůžička, , 1997bRůžička, , 1998Růžička, , 2010Mendel et al, 1997Mendel et al, , 2004Boo et al, 1998Boo et al, , 1999Boo et al, , 2003Bakthavatsalam & Singh, 1999;Nelson et al, 2001;Canard & Volkovich, 2001;Penny, 2002;Branco et al, 2006aBranco et al, , 2006bSchwartzberg et al, 2008;Koczor et al, 2010Koczor et al, , 2015.…”
Section: Datos Generales Sobre Su Biología Comportamiento Estadios unclassified
“…Several studies have reported on the attractive effect of aphid sex pheromone components (enantiomers of nepetalactol and nepetalactone) to green lacewings; e.g., Chrysopa, Peyerimhoffina and Nineta species (Boo et al 1998Hooper et al 2002;Koczor et al 2010;Weihrauch 2006;Zhang et al 2004Zhang et al , 2006aZhu et al 2005). Hence, from a practical point of view, the combination of aphid sex pheromone compounds and the ternary floral bait could yield benefits by attracting a wider range of predatory insects.…”
Section: Introductionmentioning
confidence: 97%
“…funnel traps were used (produced by Plant Protection Institute, CAR, HAS, Budapest, Hungary), which proved to be suitable for catching green lacewings (Tóth et al 2006(Tóth et al , 2009Koczor et al 2010).…”
Section: Experimental Designmentioning
confidence: 99%
“…A ternary bait comprising synthetic floral compounds was also developed, which showed higher attractiveness to C. carnea-complex adults than previously published attractants (Tóth et al 2009). Unlike several other green lacewing attractants, the ternary floral bait attracted females as well (Tóth et al 2009;Koczor et al 2010). Furthermore, it was found that females laid their eggs on baited traps (Tóth et al 2009;Jaastad et al 2010) and in the vicinity of the baits (Koczor et al 2015).…”
Section: Introductionmentioning
confidence: 95%